W poszukiwaniu sensu śmierci. O współczesnych zaświatach - Topp, Izolda (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
his article is concerned with the meaning of death in representations of the other world in modern culture. The images of life after death, which are derived from religious traditions, are transformed as a result of the process of desacralization. Changes in the traditional iconography of the other world as well as its new representations in the media and popular culture (particularly in fi lms), can be discussed either in terms of saving the symbolic meaning of death or losing its importance in modern culture. Having studied certain examples, the author concludes that the search for the meaning of death inthe present is less connected with traditional or modern representations of the other worldthen with the human experience.